MEMBANGUN COMPETITIVE ADVANTAGE DUNIA PENDIDIKAN MELALUI TEKNOLOGI INFORMASI - Sukirno DS (Jurnal Pendidikan Akuntansi Indonesia, 2004)
Rapid development of information technology will influence continouesly on education organization in all the side of world. Information technology offers many advantages to the organization needs to promote service quality or productivity. This paper discuss about meaning, adption and implication of information technology in education sector. The institution can make better plan and action in learning and teaching, research development, student services, and public service mission. By adopting information technology, in turn, the education instituion will have competitive advantage. By adopting information technology, it is hoped that education institution could achieve goals and  could create customer satisfacition.   Key Word : competitive advantage,pendidikan, teknologi informasi